Annual and seasonal variability of greenhouse gases fluxes over coastal urban and suburban areas in Portugal: Measurements and source partitioning. (15th February 2020) - Salgueiro, Vanda; Cerqueira, Mário; Monteiro, Alexandra; Alves, Célia; Rafael, Sandra; Borrego, Carlos; Pio, Casimiro
Abstract: Fluxes of CO2, H2 O and energy were measured continuously during a four-year period by eddy covariance, simultaneously at an urban and a suburban sites in the western coast of Portugal. The parallel measurements permitted to distinguish anthropogenic from natural CO2 emission/deposition. Natural CO2 fluxes were important in the suburban location. Anthropogenic emission of CO2 dominated the urban fluxes, being the double in winter by comparison with summer periods. A weekly and daily pattern was observed for CO2 fluxes in the urban area, with lower emission rates during weekends and daily flux peaks coincident with traffic rush hours. At the suburban site, daily and seasonal variability was consistent with the vegetation photosynthesis activity and growth cycles. Measured fluxes compared very favourably with inventory calculations indicating that traffic and home heating are the main causes of CO2 anthropogenic emissions. Individual CO2 fluxes measured in Portugal are at the lower side of the urban anthropogenic individual fluxes published worldwide, possibly as result of the mild local climate and low family income that hinders residential heating during cold spells. Although it rained 20% more at the urban area, by comparison with the suburban location, fluxes of water vapour were, on average, 20% higher at the suburban site, probably as result of the more porous character of the ground coverage. This affected the way energy fluxes are distributed between sensible and latent heat at each site, with higher Bowen ratios at the urban area. No heat island effect could be detected, on a seasonal basis, at the urban site, probably because of higher turbulence in the urban area caused by coastal winds and higher surface roughness. Highlights: Urban and sub-urban CO2 and H2O fluxes show a marked seasonal pattern. Urban CO2 fluxes have a strong daily and weekly variability. Measured fluxes compare very well with inventory estimations. Individual emission profiles for humans and vegetation are modelled from data.